Questioning Canvas Capital: Risks and Resilience in Art Markets - Sargentis, G.-Fivos; Papadodimas, Nikolaos (Cultural Arts Research and Development, 2025)
Art has transitioned from a medium of ideological expression and patronage in historical contexts to a formalized financial asset within the modern global market. This paper examines historical paradigms of art investment, analyzing patronage models from ancient civilizations to the Renaissance and into the contemporary era, while evaluating art's role as capital, its vulnerabilities during periods of crisis, and its interplay with power structures and meritocracy. Through case studies of key figures and eras—such as Phidias in ancient Greece, Michelangelo under the Medici, and Picasso—we explore how art's economic value is influenced by factors like market fluctuations, societal shifts, and strategic allocation of financial resources. The analysis highlights art's advantages as a diversification tool with low correlation to traditional asset classes and its potential as an inflation hedge, but also acknowledges its inherent risks, including subjectivity, illiquidity, and destruction during times of conflict. Additionally, the paper argues that enduring cultural legacies stem not from wealth alone but from meritocratic patronage and strategic investments that prioritize artistic autonomy over spectacle. By situating these findings within broader historical and economic narratives, this study sheds light on how art functions simultaneously as a cultural symbol and a financial instrument. Ultimately, it contributes insights into optimizing cultural investments at the nexus of culture, capital, and state ambition in the 21st century.